ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN GO PUBLIC DI INDONESIA (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2015-2017) - Salwa Puji Hastuti; Imam Ghozali (Diponegoro Journal of Accounting, 2019)
The aims of this study to discuss the relationship of internal factor of bank profitability. The independent variable in this research are bank size, capital ratio, loan ratio, deposits, and loan loss provissions. While the dependent variable used in this study is return on equity.This study uses secondary data from annually report of banking company listed on the Indonesia Stock Exchange. The population in this research is banking company listed on the BEI 2015-2017. The sampling method used is purposive sampling. Total sample of this research 126.This study uses panel data analysis to test the relationship between independent variable and dependent variable. The results showed that the level of bank size has a positively related to bank profitability, capital ratio, loan ratio, deposits not influenced on bank profitability, and loan loss provisions has a negatively related to bank profitability (ROE).